Knowledge Sharing sebagai mediasi Gaya Kepemimpinan Untuk Meningkatkan Prestasi Belajar Di Al-Banjari ZEROFAZA Grub Sidoarjo: Knowledge Sharing as a Mediating Leadership Style to Improve Learning Achievement at Al Banjari Zerofaza Grub Sidoarjo - hanafi, khafid khoirul; Ayu lucy larassaty; Sumartik (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to 1) determine the direct effect of leadership style, 2) the full effect of shared knowledge mediated leadership style to improve learning achievement in Albanjari Zerofaza Sidoarjo grub. The research method used is a descriptive quantitative method using the PLS 3.0 analysis tool to measure the results of knowledge sharing as mediation of leadership style to improve learning achievement at Al-Banjari Zerofaza grub Sidoarjo. This research uses descriptive analysis with 40 respondents with a purposive sampling technique. The results of the study show that knowledge sharing as a mediation of leadership style to improve learning achievement at albanjari zerofaza grub Sidoarjo can be said to be quite good. Leadership style has a positive and significant influence on learning achievement through knowledge sharing at albanjari zerofaza grub sidoarjo